Local time at zero for arratia flow - Chernega, P. P. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study the Arratia flow $x(u,t)$. We prove that $x(·,t)$ is a Markov process whose phase space is a certain subset $K$ of the Skorokhod space. We introduce the notion of total local time at zero for the Arratia flow.We prove that it is an additive, nonnegative, continuous functional of the flow and calculate its characteristic.